2018
DOI: 10.1021/acscatal.8b04348
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of gem-Difluoroalkenes via Nickel-Catalyzed Reductive C–F and C–O Bond Cleavage

Abstract: By merging C–O and C–F bond cleavage in cross-electrophile coupling, we developed a method for efficient synthesis of gem-difluoroalkenes with an alkoxy-substituent on the homoallylic position using easily accessible acetals as coupling partners with α-trifluoromethyl alkenes. Remarkably, this Ni-catalyzed allylic defluorinative cross-coupling reaction demonstrates high tolerance of a wide range of sensitive functional groups and proves to be applicable in late-stage functionalization of structurally complex c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(40 citation statements)
references
References 59 publications
1
38
1
Order By: Relevance
“…In this dual catalytic reaction, titanium(III) is capable of promoting carbon-halide bond activation to generate Besides exploiting alkyl halides as coupling partners, [41] Wang reported a Ni-catalyzed reductive CÀ F and CÀ O bond cleavage of α-trifluoromethyl alkenes 118 and acetals 119, affording functionalgroup-rich gem-difluoroalkenes 121 with an alkoxysubstituent on the homoallylic position with the assistance of trimethylsilyl chloride (TMSCl) (Scheme 25). [42] Mechanistic studies revealed that the crucial TMSCl plays an important role in the cleavage of the CÀ O bond in acetals.…”
Section: Alkylationmentioning
confidence: 99%
“…In this dual catalytic reaction, titanium(III) is capable of promoting carbon-halide bond activation to generate Besides exploiting alkyl halides as coupling partners, [41] Wang reported a Ni-catalyzed reductive CÀ F and CÀ O bond cleavage of α-trifluoromethyl alkenes 118 and acetals 119, affording functionalgroup-rich gem-difluoroalkenes 121 with an alkoxysubstituent on the homoallylic position with the assistance of trimethylsilyl chloride (TMSCl) (Scheme 25). [42] Mechanistic studies revealed that the crucial TMSCl plays an important role in the cleavage of the CÀ O bond in acetals.…”
Section: Alkylationmentioning
confidence: 99%
“…The C–F bond is one of the strongest σ covalent single bonds, and its activation typically requires the transition metal catalysis (TMs) (Huang et al, 2018; Lin et al, 2019). In last decades, the functionalization of C–F bonds has received considerable interest, and extensive efforts have been made to develop various strategies for the C–F activation (Mazurek and Schwarz, 2003; Panetier et al, 2011; Johnson et al, 2012; Klahn and Rosenthal, 2012; Nova et al, 2012; Kuehnel et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Although we did not obtain the one fluoroalkyl accommodated nickel complex [(bipy)Ni(CH 2 CF 3 )(I)] 1 which showed more structural similarities to the reported [(bipy)Ni( o -tolyl)Cl] precatalyst,14 b we presumed that β-fluorine elimination16 of [(bipy)Ni(CH 2 CF 3 ) 2 ] 2 hinted by the C–F bond length analysis could be leveraged for the in situ generation of [(bipy)Ni(F)(CH 2 CF 3 )] 2a with concurrent extrusion of vinylidenedifluoride (CH 2 CF 2 ). Notably, the Ni–F structural motif of intermediate 2a was supposed to facilitate the transmetalation of arylboronic acids towards nickel according to a recent example of base-free Suzuki coupling 4 g .…”
Section: Resultsmentioning
confidence: 65%